WiFlock: Collaborative group discovery and maintenance in mobile sensor networks - Purohit, A; Priyantha, B; Jie Liu (2011 10th International Conference on Information Processing in Sensor Networks, 2011)
Low energy neighbor discovery, group formation, and group maintenance is a fundamental service in mobile sensor networks. Traditional solutions consider these protocols separately. In this paper, we introduce WiFlock, an energy-efficient protocol that combines discovery and maintenance using a collaborative beaconing mechanism. WiFlock combines a coordinated synchronized listening and evenly-spaced transmission (SLEST) schedule effectively with oneway discovery beacons to fulfill both purposes. We show that shorter listening duration implies smaller discovery latency and faster group information propagation. Using a novel carrier sensing technique, we achieve a fast wakeup and listen duration of 80μs on a low-power radio. With this listening duration, we evaluate WiFlock on a 50-node test bed with nodes running at 0.2% duty cycles. We show that WiFlock has shorter discovery latency and better scalability than previous approaches.